Preeclampsia and cardiovascular disease: interconnected paths that enable detection of the subclinical stages of obstetric and cardiovascular diseases - Valdés G (Dove Medical Press, 2017)
Gloria Valdés Department of Nephrology, Facultad de Medicina, Pontificia Universidad Católica, Santiago, Chile Abstract: The potent and now longstanding evidence of the association between placentation-related disorders and cardiovascular disease should be translated into clinical practice in order to introduce a preventive approach to future obstetric and cardiovascular diseases. The purpose of this review is to integrate cardiovascular risk/disease and obstetric complications, which are linked by endothelial dysfunction, as windows of opportunity for improving women’s health. Questionnaires adaptable to local practices are proposed to incorporate cardiovascular and obstetrical indexes into two stages of a woman’s lifetime. Keywords: pregnancy, preeclampsia, placentation-related disorders, cardiovascular disease, cardiovascular stress test, prevention, endothelial dysfunction, women’s health